The Development of Kindergarten Teacher’s Personality Through Knowledge Sharing During The Covid-19 Pandemic - Evrilia Silvia Ningrum; Suryanto Suryanto (Faculty of Teacher Training and Education, Universitas Terbuka, 2021)
Covid-19 pandemic has had a significant impact on education, as well as occured in early childhood education where the learning process is conducted online. Changes in the learning process that suddenly happened makes teachers don’t have the readiness to change even a teacher who holds an essential role in education is required to have the readiness to face change. Hence, the teacher must have personality competence to support the learning process’s success. This study discusses kindergarten teacher’s personality development through knowledge sharing in dealing with the learning process’s changes during the Covid-19 pandemic. The methodology in this study used a qualitative approach with case study type and descriptive data analysis technique. The data were collected through the deep interview method, and the informants were the principal and four teachers of Kartini Amadanom Kindergarten. The result of this study indicated that knowledge sharing made a positive contribution to teacher’s personality development endeavors. In other words, if knowledge sharing with teachers is conducted well, the teacher’s personality development endeavor well. This study has limitations, such as the fact that the research scope is limited to one school. In further research, researchers can discover further a teacher’s personality development through knowledge sharing by comparing to data from other schools and adding it as another method to accelerate the development of teachers’ personalities. This study gives an alternative solution to develop the teacher’s personality to confront online learning as an effect of the Covid-19 pandemic. The result of knowledge sharing aims to arrange the process of online learning.